PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DENGAN MODEL PEMBELAJARAN BRAIN BASED LEARNING BERBANTUAN BRAIN GYM - Rahayu, Nur Fitriya; Hadi, Wiwin Puspita; Wahyuni, Eva Ari; Sutarja, Maria Chandra; Hartiningsih, Try (Natural Science Education Research, 2023)
This research aimed at differences in students' critical thinking skills before and after implementation of the Brain Based Learning model assisted by Brain Gym. The method used in this study is an experimental method with a Pre-Experimental One Group Pretest-Posttest Design. The sample in this study ware students class VIII SMP Muhammadiyah 05 Bungah amounted to 18 students of the third semester og 2022/2023. Hypothesis analysis technique was paired sample t-test. Data-up technique trough used critical thinking skills test. The average value of the pretest value is 44,62 while the average value of the posttest value is 77,28.  Based on the result hypothesis testing obtained a significance value of 0.000 less than 0.05 then H0 is rejected and H1 is accepted, meaning there was differences in critical thinking skills before and after implementation of the Brain Based Learning model assisted by Brain Gym. Then the average N-Gain result of 0.6 in the medium category.